Investigation of Integral and Differential Characteristics of Variatropic Structure Heavy Concretes by Ultrasonic Methods - Levon R. Mailyan; Sergey A. Stel’makh; Evgenii M. Shcherban’; Alexander K. Khalyushev; Alla S. Smolyanichenko; Alexander K. Sysoev; Ivan A. Parinov; Alexander V. Cherpakov (Applied Sciences, 2021)
The article develops methods and methodology for experimental studies of centrifuged and vibro-centrifuged concrete products of annular cross-section. They assess the real variatropy of the structure and confirm the correctness of the accepted research. An original technique for experimental studies of the variatropy of the cross-sections of vibrated, centrifuged and vibro-centrifuged concretes is proposed to determine their integral (common) and differential (differing in layers) strength and strain characteristics and deformation diagrams. It has been proved that with vibro-centrifugation it becomes possible to obtain concretes with improved structure and higher characteristics compared with centrifugation and vibration techniques. Experimental studies of the differential characteristics of centrifuged and vibro-centrifuged concretes under compression and tension revealed that the outer layer of concrete had the best characteristics after centrifugation and vibro-centrifugation, and the inner layer had the worst ones. The three-layer model of the variatropic structure for centrifuged and vibro-centrifuged concrete has been experimentally confirmed. The concrete of the outer layers had the highest strength and modulus of elasticity and the least deformability; the concrete of the inner layers had the lowest strength and modulus of elasticity and the highest deformability; and the concrete of the middle layers had average characteristics. The deformation diagrams of centrifuged and vibro-centrifuged concretes were also differentiated by layers, confirming the variatropy of the structure of such concretes. The deformation diagrams for the outer concrete layer demonstrated the highest strength; the diagrams for the inner concrete layer showed the lowest strength; and the diagrams for the middle concrete layer corresponded to mean characteristics.